Journalism and ideology of culture: the conflicts between indigenous people and rural producers in Mato Grosso do Sul - Silva, Marcos Paulo da; Raposo, Maurício de Melo (MATRIZes, 2021)
The article intends to understand fact-framing about conflicts between indigenous ethnic groups and rural producers in Correio do Estado, the main Mato Grosso do Sul state newspaper, adopting as a reference point the murder of the indigenous leader Semião Vilhalva, from the Guarani and Kaiowá ethnic groups, in August 2015. From the theoretical perspective of framing analysis, five editorials and five opinion articles published from August to October 2015 are studied as an empirical basis, identifying, in the newspaper’s contemporary rhetoric, symbolic and cultural elements related to the “ideology of the Mato Grosso do Sul culture”, a concept forged by regional elites since the 1930s.